2020
DOI: 10.1136/annrheumdis-2019-216648
|View full text |Cite
|
Sign up to set email alerts
|

BCP crystals promote chondrocyte hypertrophic differentiation in OA cartilage by sequestering Wnt3a

Abstract: ObjectiveCalcification of cartilage with basic calcium phosphate (BCP) crystals is a common phenomenon during osteoarthritis (OA). It is directly linked to the severity of the disease and known to be associated to hypertrophic differentiation of chondrocytes. One morphogen regulating hypertrophic chondrocyte differentiation is Wnt3a.MethodsCalcification and sulfation of extracellular matrix of the cartilage was analysed over a time course from 6 to 22 weeks in mice and different OA grades of human cartilage. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Calciumcontaining crystals, which encompass basic calcium phosphate (BCP) and calcium pyrophosphate dihydrate crystals (CPPD), have been demonstrated to be of etiologic importance in OA. Indeed they were shown to actively trigger inflammatory, catabolic and oxidant responses in joint cells such as synovial fibroblasts, macrophages, osteoclasts and chondrocytes (Fuerst et al, 2009;Nasi et al, 2016b;Bertrand et al, 2020;Yan et al, 2020). However, the receptors and signaling pathways modulating ectopic calcification in OA joints only start to be elucidated (Castelblanco et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Calciumcontaining crystals, which encompass basic calcium phosphate (BCP) and calcium pyrophosphate dihydrate crystals (CPPD), have been demonstrated to be of etiologic importance in OA. Indeed they were shown to actively trigger inflammatory, catabolic and oxidant responses in joint cells such as synovial fibroblasts, macrophages, osteoclasts and chondrocytes (Fuerst et al, 2009;Nasi et al, 2016b;Bertrand et al, 2020;Yan et al, 2020). However, the receptors and signaling pathways modulating ectopic calcification in OA joints only start to be elucidated (Castelblanco et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This mutation also delayed development of the left acetabulum and left glenoid fossa, as observed by Alcian blue staining in 8-week-old knock-in mutant mice [5]. Feldeman et al found that MMP13, which is related to chondrogenesis [18], was overexpressed in femur-derived bone cells of knock-in mice [5]. Previous studies showed that TENM3 is related to cartilage formation and expressed in prechondrogenic mesenchymal cells.…”
Section: Discussionmentioning
confidence: 89%
“…However, CPPD crystals themselves did only induce a minor increase in p16 expression, but have no change in the amount of β-Gal-positive cells (Figure 3C). BCP crystals have been shown to induce hypertrophic differentiation of chondrocytes by activating the canonical Wnt signaling pathway (Bertrand et al, 2020). However, no effect of BCP crystals on chondrocyte senescence markers was detected (Figure 3C).…”
Section: Discussionmentioning
confidence: 94%
“…Sterile, pyrogen-free BCP crystals were synthesized as previously described (Bertrand et al, 2020). Triclinic CPPD crystals were purchased from InvivoGen.…”
Section: Basic Calcium Phosphate and Calcium Pyrophosphate Dihydrate Crystal Stimulationmentioning
confidence: 99%
See 1 more Smart Citation